Special needs in the early years partnership and participation - Crutchley, Rebecca (Los Angeles SAGE, 2018)
Fully up to date with the SEND Code of Practice, this book explores all the key contemporary issues relevant to supporting children with special needs in an early years context. Combining theory with practice, it demonstrates how to ensure children's individual needs are at the heart of early years provision.
Legislation and policy: towards a participatory partnership / Rebecca Crutchley -- Working with parents: principles of engagement / Louise Arnold -- Pupil and parent voice: contributions to assessment and planning / Rebecca Crutchley -- Models of SEN provision: the inclusion debate / Ruth Hunt -- Leadership and inclusion: creating and ethos, culture and provision / Athina Tempriou -- Professional ethics: partnership and collaboration in early years / Beate Hellawell -- Early intervention and transition / Rebecca Crutchley and Ruth Hunt -- CPD opportunities for staff working with children with SEND in the early years / Ruth Hunt and Anna Newbold -- Multi-agency working: partnership and collaboration / Estelle Martin.
Includes bibliographical references (pages 169-185) and index.
Keywords: Special education -- Great Britain; Children with disabilities -- Education (Early childhood) -- Great Britain